Influence of RANEY Nickel on the Formation of Intermediates in the Degradation of Lignin - Daniel Forchheim; Ursel Hornung; Philipp Kempe; Andrea Kruse; David Steinbach (International Journal of Chemical Engineering)
Lignin forms an important part of lignocellulosic biomass and is an abundantly available residue. It is a potential renewable source of phenol. Liquefaction of enzymatic hydrolysis lignin as well as catalytical hydrodeoxygenation of the main intermediates in the degradation of lignin, that is, catechol and guaiacol, was studied. The cleavage of the ether bonds, which are abundant in the molecular structure of lignin, can be realised in near-critical water (573 to 673 K, 20 to 30 MPa). Hydrothermal treatment in this context provides high selectivity in respect to hydroxybenzenes, especially catechol. RANEY Nickel was found to be an adequate catalyst for hydrodeoxygenation. Although it does not influence the cleavage of ether bonds, RANEY Nickel favours the production of phenol from both lignin and catechol. The main product from hydrodeoxygenation of guaiacol with RANEY Nickel was cyclohexanol. Reaction mechanism and kinetics of the degradation of guaiacol were explored.